2020
DOI: 10.3390/app10228297
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Potential of Mangiferin on Glucansucrase Producing Streptococcus mutans Biofilm in Dental Plaque

Abstract: Glucansucrase secreted by Streptococcus mutans and composed of virulence genes alters oral microbiota, creating adherent environment for structural bacteria colony forming dental biofilm. The present investigation studied the inhibitory and binding potentials of mangiferin against S. mutans and its enzyme glucansucrase implicated in biofilm formation. Antibacterial activity against planktonic S. mutans was carried out. Using reverse transcription PCR, the expression of crucial virulence genes, gtfB, gtfC, gtfD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 59 publications
(79 reference statements)
0
6
0
Order By: Relevance
“…Mangiferin has a wide range of pharmacological effects, such as immunomodulatory, anti‐HIV, antibacterial, and antiviral activities, which can prevent tissue damage by inhibiting inflammation and oxidative stress 20 . It inhibits Streptococcus mutans biofilm formation by attenuating glucan sucrase activities 21 . Mangiferin exhibited the lowest MIC values for S. aureus and M. catarrhalis in our study, which indicated that the most sensitive inhibition concentration used was 0.25 mg/mL.…”
Section: Resultsmentioning
confidence: 68%
“…Mangiferin has a wide range of pharmacological effects, such as immunomodulatory, anti‐HIV, antibacterial, and antiviral activities, which can prevent tissue damage by inhibiting inflammation and oxidative stress 20 . It inhibits Streptococcus mutans biofilm formation by attenuating glucan sucrase activities 21 . Mangiferin exhibited the lowest MIC values for S. aureus and M. catarrhalis in our study, which indicated that the most sensitive inhibition concentration used was 0.25 mg/mL.…”
Section: Resultsmentioning
confidence: 68%
“…The structure of thidiazuron (PubChem CID: 40087) used in this study was retrieved from pubchem database (https://pubchem.ncbi.nlm.nih.gov/compound/) as .sdf format and latter converted to .pdb format using PyMOL software. Docking calculations were executed using AutoDock (version 1.5.2 revision 2) as described in the literature [17,18]. The docked conformations of each ligand were ranked into clusters based on the binding energy and the top ranked conformations were visually analyzed with pymol.…”
Section: Methodsmentioning
confidence: 99%
“…Plates were then rocked in 95% ethanol at room temperature for 30 mins and absorbance recorded at the wavelength of 595 nm [18].…”
Section: Inhibitory Potential Of Thidiazuron Against C Albicans Bio Lmmentioning
confidence: 99%
“…The structure of thidiazuron (PubChem CID: 40087) used in this study was retrieved from pubchem database (https://pubchem.ncbi.nlm.nih.gov/compound/) as .sdf format and latter converted to .pdb format using PyMOL software. Docking calculations were executed using AutoDock (version 1.5.2 revision 2) as described in the literature (Morris et al 2009;Emeka et al 2020). The docked conformations of each ligand were ranked into clusters based on the binding energy and the top ranked conformations were visually analyzed with PyMOL software.…”
Section: Preparation Of Protein Ligand and Molecular Docking Studymentioning
confidence: 99%
“…Then, the unbound stains were removed and the wells were washed with sterile distilled water. Plates were then rocked in 95% ethanol at room temperature for 30 min and absorbance recorded at the wavelength of 595 nm (Emeka et al 2020).…”
Section: Inhibitory Potential Of Thidiazuron Against C Albicans Bio Lmmentioning
confidence: 99%